Viral-Induced Enhanced Disease Illness - Smatti, Maria K.; Al Thani, Asmaa A.; Yassine, Hadi M. (Frontiers in Microbiology, 2018)
Understanding immune responses to viral infections is crucial to progress in the quest for ‎effective infection prevention and control. The host immunity involves various mechanisms to ‎combat viral infections. Under certain circumstances, a viral infection or vaccination may result in ‎a subverted immune system, which may lead to an exacerbated illness. Clinical evidence of ‎enhanced illness by preexisting antibodies from vaccination, infection or maternal passive ‎immunity is available for several viruses and is presumptively proposed for other viruses. ‎Multiple mechanisms have been proposed to explain this phenomenon. It has been confirmed that ‎certain infection- and/or vaccine-induced immunity could exacerbate viral infectivity in Fc ‎receptor- or complement bearing cells- mediated mechanisms. Considering that antibody ‎dependent enhancement (ADE) is a major obstacle in vaccine development, there are continues ‎efforts to understand the underlying mechanisms through identification of the epitopes and ‎antibodies responsible for disease enhancement or protection. This review discusses the recent ‎findings on virally induced ADE, and highlights the potential mechanisms leading to this ‎condition. ‎